Screening and identification of strains for high quality and antioxidant activity of Baijiu from strong-flavor Daqu and analysis of microbial synergistic effects - Ruoyu Mi; Wei Lu; Xuan Zhang; Feng Yan; Beizhong Han; Qingyang Liu; Anjun Li; Ping Liu (PLoS ONE, 2025)
In this study, functional strains with strong fermentation characteristics were isolated from Strong-flavor Daqu and evaluated for their ability to enhance the quality and antioxidant activity of Baijiu. Bacillus velezensis (S1), Bacillus subtilis (S12), and Escherichia coli (S16) were identified as key strains. Fermentation experiments with different inoculation amounts and combinations revealed synergistic effects on Baijiu quality and antioxidant activity. Specifically, the total ester content in Baijiu fermented with 3% of S1, S12 and S16 were increased by 5.68%, 53.41% and 70.45% respectively, while the DPPH radical scavenging rate was increased by 52.01%, 17.63% and 35.52%, respectively, compared with the Baijiu fermented only with Daqu. Multi-strain combinations, particularly 4%-S16+2.5%-S1 and 3%-S16+4%-S12, exhibited notable antioxidant activity and ester content. Furthermore, the inoculation of 3% E. coli, 2% B. velezensis and 4% B. subtilis combination significantly increased total ester content (1.94 g/L) and antioxidant activity (38.09%) of Baijiu, in which S1 increased antioxidant activity of Baijiu while S12 increased total ester content. The results of GC-MS indicated that biofortified fermentation produced high levels of esters and guaiacol and its analogues, facilitated by synergistic interactions among indigenous microorganisms. This study is helpful to provide a new perspective and insight for improving Baijiu flavor and antioxidant activity.